High-power 55-fs Yb:YAG thin-disk oscillator at 200 MHz repetition rate - Liu, Heyan; Yang, Tingting; Xu, Jia; Wang, Qing; Xuan, Hongwen; Zhang, Jinwei (Frontiers in Physics, 2022)
High-repetition-rate ultrafast laser oscillators with high average power and short pulse duration provide excellent sources for generating optical frequency combs. Here we report a Kerr-lens mode locked Yb:YAG thin-disk oscillator delivering 203-MHz pulses at an average power of 9.4 W. A single additional nonlinear plate was inserted inside the cavity to enhance the Kerr lens effect, which leads to a substantial broadening of the mode-locked spectrum. The resultant pulse duration is 55 fs. The demonstrated oscillator combines a high repetition rate, a high average power and short pulse duration within one resonator, offering an ideal prerequisite for the optical-frequency metrology and frequency-comb spectroscopy with high signal-to-noise ratio.